2005
DOI: 10.1007/s11099-005-0060-8
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence imaging of photosynthetic activity with the flash-lamp fluorescence imaging system

Abstract: A flash-lamp chlorophyll (Chl) fluorescence imaging system (FL-FIS) is described that allows to screen and image the photosynthetic activity of several thousand leaf points (pixels) of intact leaves in a non-destructive way within a few seconds. This includes also the registration of several thousand leaf point images of the four natural fluorescence bands of plants in the blue (440 nm) and green (520 nm) regions as well as the red (near 690 nm) and far-red (near 740 nm) Chl fluorescence. The latest components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 50 publications
4
78
1
1
Order By: Relevance
“…Several studies have consistently shown that RF/FRF is a good inverse indicator of the chlorophyll content [10,18,61]. However, our results show that BF/FRF (BFRR_UV) yielded the highest correlation with LCC (Figure 5c), suggesting that the BF/FRF (BFRR_UV) can serve as an indicator of the leaf chlorophyll.…”
Section: Estimation Of Lccmentioning
confidence: 48%
“…Several studies have consistently shown that RF/FRF is a good inverse indicator of the chlorophyll content [10,18,61]. However, our results show that BF/FRF (BFRR_UV) yielded the highest correlation with LCC (Figure 5c), suggesting that the BF/FRF (BFRR_UV) can serve as an indicator of the leaf chlorophyll.…”
Section: Estimation Of Lccmentioning
confidence: 48%
“…Chlorophyll a fluorescence kinetics (CF) allows determining whether the photosynthetic apparatus was damaged after cessation of watering. Fluorescence methods have been successfully applied in many studies related to plant drought resistance (Lichtenthaler and Babani 2004;Lichtenthaler et al 2005;Hura et al 2007;Rapacz et al 2010);Yin et al 2010). CF-modulated parameters are commonly used in the JIP-test.…”
Section: Line Grain Number (Gn) Grain Weight (G) (Gw) Shoot Biomass (mentioning
confidence: 99%
“…Therefore, the availability of inorganic phosphate plays a significant role for acclimation to such adverse conditions. High temperature stress directly or indirectly affects plant photosynthetic functions by changing the structural organization and physico-chemical properties of thylakoid membranes (Lichtenthaler et al 2005). The rate of photorespiration increases with increasing temperature which reduces net photosynthesis and probably the seed yield of the crop.…”
Section: Discussionmentioning
confidence: 99%